2018
DOI: 10.1155/2018/9529821
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Adverse Event Associated with Olaparib Therapy in a Patient with Metastatic Breast Cancer

Abstract: Olaparib was first FDA approved for use in women with advanced ovarian cancer and germline BRCA mutations. Based on the results of subsequent research, the use of this drug has been expanded to patients with metastatic breast cancer with germline BRCA mutation. With the use of a relatively new medication and a larger patient population eligible for therapy, monitoring for novel adverse events associated with therapy is important. This case represents a patient with metastatic breast cancer and germline BRCA2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Erythema nodosum may arise from a delayed hypersensitivity response 23 . In the abovementioned case report of olaparib for metastatic BC, erythema nodosum lessened after switching from capsule to tablet formulation, which the authors suggested could be related to the higher bioavailability and longer half‐life of the tablet formulation 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erythema nodosum may arise from a delayed hypersensitivity response 23 . In the abovementioned case report of olaparib for metastatic BC, erythema nodosum lessened after switching from capsule to tablet formulation, which the authors suggested could be related to the higher bioavailability and longer half‐life of the tablet formulation 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a case of metastatic BC responding to olaparib at 300 mg BID reported erythema nodosum as a novel AE 23 . The nodules resolved completely after withholding olaparib and applying prednisone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRCA1 and BRCA2 are well-characterized genes involved in homologous recombination repair, and BRCA1 mutation was detected in the present case. Since olaparib is a newly approved drug, case reports of olaparib-induced skin disorders are limited; only erythema nodosum and cutaneous arteritis have been previously reported [3][4][5]. Notably, these previous reports indicate that skin lesions mainly appear on the extremities [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…The median onset time of reported adverse events was 61 days; most events occurred in the first 3 months since olaparib initiation. Other novel adverse events have been described in case reports of patients with MBC with a BRCA1/2 mutation, including recurrent episodes of erythema nodosum, which may be managed through dose reductions [ 40 ].…”
Section: Introductionmentioning
confidence: 99%